Genome-wide RNAi screen reveals a new role of a WNT/CTNNB1 signaling pathway as negative regulator of virus-induced innate immune responses. - Martin Baril; Salwa Es-Saad; Laurent Chatel-Chaix; Karin Fink; Tram Pham; Valérie-Ann Raymond; Karine Audette; Anne-Sophie Guenier; Jean Duchaine; Marc Servant; Marc Bilodeau; Eric Cohen; et al. (PLoS Pathogens, 2013)
To identify new regulators of antiviral innate immunity, we completed the first genome-wide gene silencing screen assessing the transcriptional response at the interferon-β (IFNB1) promoter following Sendai virus (SeV) infection. We now report a novel link between WNT signaling pathway and the modulation of retinoic acid-inducible gene I (RIG-I)-like receptor (RLR)-dependent innate immune responses. Here we show that secretion of WNT2B and WNT9B and stabilization of β-catenin (CTNNB1) upon virus infection negatively regulate expression of representative inducible genes IFNB1, IFIT1 and TNF in a CTNNB1-dependent effector mechanism. The antiviral response is drastically reduced by glycogen synthase kinase 3 (GSK3) inhibitors but restored in CTNNB1 knockdown cells. The findings confirm a novel regulation of antiviral innate immunity by a canonical-like WNT/CTNNB1 signaling pathway. The study identifies novel avenues for broad-spectrum antiviral targets and preventing immune-mediated diseases upon viral infection.